2021
DOI: 10.3390/brainsci11050661
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profile of Saliva in Parkinson’s Disease Patients: A Proof of Concept Study

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder. It affects many organs. Lewy bodies—a histopathological “hallmark” of PD—are detected in about 75% of PD submandibular gland samples. We hypothesize that saliva can be a source of biomarkers of PD. The aim of the study was to evaluate and compare the salivary proteome of PD patients and healthy controls (HC). Salivary samples from 39 subjects (24 PD patients, mean age 61.6 ± 8.2; 15 HC, mean age 60.9 ± 6.7) were collected. Saliva was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 68 publications
(71 reference statements)
0
17
3
Order By: Relevance
“…Moreover, the up-regulated/down-regulated miRNAs in PD samples are enriched in fatty acid biosynthesis pathways. Additionally, we have found that putative PD biomarkers in urine and saliva have received extensive attention from researchers ( Ho et al, 2014 ; Fraser et al, 2016 ; Cressatti et al, 2020 ; Figura et al, 2021 ). However, there are few reports on the investigation of exosomal ncRNA.…”
Section: The Diagnostic Implications Of Exosomal Non-coding Rna On Pa...mentioning
confidence: 99%
“…Moreover, the up-regulated/down-regulated miRNAs in PD samples are enriched in fatty acid biosynthesis pathways. Additionally, we have found that putative PD biomarkers in urine and saliva have received extensive attention from researchers ( Ho et al, 2014 ; Fraser et al, 2016 ; Cressatti et al, 2020 ; Figura et al, 2021 ). However, there are few reports on the investigation of exosomal ncRNA.…”
Section: The Diagnostic Implications Of Exosomal Non-coding Rna On Pa...mentioning
confidence: 99%
“…Moreover, a discrete difference between PD patients' saliva components and those obtained from healthy controls was observed. The proteomic study by Figura et al showed that the saliva from 39 PD patients had lower concentrations of S100-A16, ARP2/3, and VPS4B than the control group [90]. These proteins are involved in various metabolic and inflammatory pathways.…”
Section: Exos As a Future Approach For Pd Diagnosismentioning
confidence: 99%
“…VPS4B is involved in the endosomal vesicular release of a subset of proteins and the EXOs secretion pathway [97]. The authors suggested that the observed decrease in VPS4B might be due to its increased uptake by EXOs [90].…”
Section: Exos As a Future Approach For Pd Diagnosismentioning
confidence: 99%
“…The S100A16 protein belongs to the S100 protein family, which is found in abundance in the brain and adipose tissue [88]. Figura et al recently discovered that the S100A16 protein concentration in Parkinson's disease patients' saliva was lower than in healthy controls [89]. This is a fascinating find, because this protein has never been explored in the context of schizophrenia.…”
Section: Schizophrenia and S100 Proteinmentioning
confidence: 99%